Modulating the blood–brain tumor barrier for improving drug delivery efficiency and efficacy. Issue 1 (31st January 2022) - Song, Yujun; Hu, Chuan; Fu, Yao; Gao, Huile
Abstract: The blood–brain barrier (BBB) is a highly regulated and efficient barrier that controls the mass transfer between blood and brain, severely limits brain penetration of systemically administered therapeutics. During the onset and progression of brain tumors, BBB alters, and the blood–brain tumor barrier (BBTB) forms. Though BBTB differs from BBB in certain aspects, such as neuronal connections and aberrant pericyte distribution, it retains critical aspects of BBB. Hence, one major challenge in the development of therapeutics for brain tumor is to achieve sufficient BBTB penetration thus improving the efficiency of drug delivery to the tumor site. In this review, we summarize the strategies that can overcome BBTB and improve BBTB penetration efficiency from the perspectives of regulating BBTB structure and transport processes. Abstract : One major challenge in the development of therapeutics for brain tumor is to achieve sufficient BBTB penetration thus improving the efficiency of drug delivery to the tumor site. In this review, the authors summarize the strategies that can overcome BBTB and improve BBTB penetration efficiency from the perspectives of regulating BBTB structure and transport processes.